Knowledge, Perception, and attitude towards medical ethics among undergraduate medical students at Jouf University, Saudi Arabia - Ibrahim, Mahrous A; Almadi, Khaled B; Alsharari, Bander D; Alsharari, Fares H; Mostafa, Enas MA (Bangladesh Journal of Medical Science, 2023)
Objectives: This study aimed to assess knowledge, perception, and attitude towards medical ethics among undergraduate medical students at College of Medicine,Jouf University (COMJU), Kingdom of Saudi Arabia (KSA). Material and Methods: A cross-sectional study was conducted on a convenience sample of 118 undergraduate medical students at Jouf University, KSA using a self-administered questionnaire that included section I (Basic demographic characteristics), section II (Knowledge about medical ethics), and section III (Perception and attitudes towards different aspects of medical ethics). Descriptive analysis was carried out. Results: More than two-thirds of the participating students were knowledgeable about different aspects of medical ethics. Despite that, about half of them did not consider confidentiality as a fundamental issue in medical ethics, and more than half accepted that a physician could ignore a patient’s privacy. About 78.2 % believed that health practitioners must comply with the ethics of their profession. Nearly 75.5 % of respondents believed that a specialized Committee should be present in the college to set ethical rules. Interestingly, 71.7 % declared that there is a necessity of incorporating medical ethics into an undergraduate curriculum. Conclusion: Our results emphasize the need for increasing the incorporation of medical ethics issues into the undergraduate medical curriculum to enhance their knowledge and strengthen their positive attitude towards medical ethics. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page :353-359